Prevalence of anxiety and depression symptoms among football players at a top level in Iceland - Emil Pálsson 1993- (2016)
Recent studies have shown that prevalence of anxiety and depression symptoms are as similar among athletes, as they are among the general public. The aim of the study was to examine the prevalence of anxiety and depression symptoms among both male and female football players in Iceland. A survey was conducted through social media and a chain referral sampling technique was used to collect the biggest sample as possible. The instruments used were two self-report questionnaires, GAD-7 to measure severity of anxiety symptoms, and PHQ-9 to measure severity of depression, alongside 8 background questions. The participants were 103 players from 22 teams playing at the highest level in Iceland. The results of the study were that 37.9% of the players had mild to severe anxiety symptoms and 45.7% had mild to severe depression symptoms. There was no gender difference on GAD-7 and PHQ-9 scores, but younger participants experienced more anxiety and depression symptoms than older participants (25 years and older). Recently injured players did not report more symptoms of depression than those who had been injury free last months and training intensity did not increase anxiety. High self-confidence correlated with fewer symptoms of both anxiety and depression. These results indicate that anxiety and depression symptoms are frequent among football players in Iceland. Keywords: football players, anxiety symptoms, depression symptoms, Nýlegar rannsóknir hafa sýnt fram á að algengi kvíða- og þunglyndiseinkenna séu í það minnsta jafn algengar meðal íþróttamanna og almennings. Rannsóknin var framkvæmd í þeim tilgangi að meta algengi kvíða- og þunglyndiseinkenna hjá knattspyrnufólki í efstu deild á Íslandi. Könnun var lögð fyrir leikmenn í gegnum internetið og snjóboltaúrtak notað til að búa til eins stórt þýði og mögulegt var. Þátttakendur voru 103 leikmenn úr 22 liðum í efstu deild karla og kvenna. Niðurstöður rannsóknarinnar voru þær að 37.9% leikmanna voru með væg til alvarleg kvíðaeinkenni og 45.7% voru með væg til alvarleg ...